2023
DOI: 10.1002/hed.27344
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune microenvironment alterations using induction cetuximab in a phase II trial of deintensified therapy for p16‐positive oropharynx cancer

Abstract: Background We sought to characterize early changes in CD8+ tumor‐infiltrating lymphocytes and tumor transcriptomes after induction cetuximab in a cohort with p16‐positive oropharyngeal cancer on a phase II clinical de‐escalation trial. Methods Tumor biopsies were obtained before and 1 week after a single cetuximab loading dose in eight patients enrolled in a phase II trial of cetuximab and radiotherapy. Changes in CD8+ tumor‐infiltrating lymphocytes and transcriptomes were assessed. Results One week after cetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…This study also evaluated pre-and post-treatment tumor samples for tumor immune infiltration and found that motolimod plus cetuximab was associated with a decreased induction of Tregs and enhanced CD8+ T cell infiltration of tumors following treatment. While this treatment-naïve group offers a better model for TLR-driven immune infiltration, this study was again limited by the lack of a control group as Cetuximab is associated with similar effects on the tumor-immune microenvironment [24]. Despite limitations of these studies, the mechanisms of TLR-agonist stimulation in clinical trials are unlikely to have relevance if they lack a treatment benefit.…”
Section: Discussionmentioning
confidence: 99%
“…This study also evaluated pre-and post-treatment tumor samples for tumor immune infiltration and found that motolimod plus cetuximab was associated with a decreased induction of Tregs and enhanced CD8+ T cell infiltration of tumors following treatment. While this treatment-naïve group offers a better model for TLR-driven immune infiltration, this study was again limited by the lack of a control group as Cetuximab is associated with similar effects on the tumor-immune microenvironment [24]. Despite limitations of these studies, the mechanisms of TLR-agonist stimulation in clinical trials are unlikely to have relevance if they lack a treatment benefit.…”
Section: Discussionmentioning
confidence: 99%